2008
DOI: 10.1007/s10995-008-0374-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Obstetrician-gynecologists’ Practices Related to HIV Testing

Abstract: Many patients did not recall that their obstetrician-gynecologist had ever recommended HIV testing, although the majority had been tested. Efforts should be made to increase communication between obstetrician-gynecologists and their patients related to HIV risk status and HIV testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…12 In a survey of patients identified by the Collaborative Ambulatory Research Network, 48% of patients reported being tested based on their obstetrician or gynecologist recommendation. 13 In a New York city community health survey, patients were more likely to have been recently tested if a doctor recommended an HIV test in the past year. 14 In a survey of adults at 9 internal medicine clinics, 92.4% of those who reported getting tested for HIV also reported that their physician had recommended HIV testing.…”
Section: Methodsmentioning
confidence: 99%
“…12 In a survey of patients identified by the Collaborative Ambulatory Research Network, 48% of patients reported being tested based on their obstetrician or gynecologist recommendation. 13 In a New York city community health survey, patients were more likely to have been recently tested if a doctor recommended an HIV test in the past year. 14 In a survey of adults at 9 internal medicine clinics, 92.4% of those who reported getting tested for HIV also reported that their physician had recommended HIV testing.…”
Section: Methodsmentioning
confidence: 99%
“…A more recent study [23] investigated patient perceptions of HIV testing. Two-thirds (65%) of patients reported having been tested for HIV at some point in the past, though 72% did not recall if their current ob-gyn recommended testing [23].…”
Section: Resultsmentioning
confidence: 99%
“…Two-thirds (65%) of patients reported having been tested for HIV at some point in the past, though 72% did not recall if their current ob-gyn recommended testing [23]. Among pregnant patients, 61% did not recall their current provider having recommended testing, though 82% had been tested at some point, with 71% receiving their test results during the current pregnancy [23]. Young, pregnant, Hispanic and African-American patients were most likely to report that HIV testing had been recommended by their obstetrician-gynecologist.…”
Section: Resultsmentioning
confidence: 99%
“…The provision of information about HIV arose as a way to increase awareness, reduce fear and stigma, and to increase HIV testing acceptance. Studies suggest that prenatal testing rates are lower when women are perceived as low risk by themselves or their providers [2, 14, 15]. …”
Section: Discussionmentioning
confidence: 99%